Association of Sugar-Sweetened Beverage Consumption with Prediabetes and Glucose Metabolism Markers in Hispanic/Latino Adults in the United States: Results from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). Issue 1 (27th October 2021) - Moon, Jee-Young; Hua, Simin; Qi, Qibin; Sotres-Alvarez, Daniela; Mattei, Josiemer; Casagrande, Sarah S; Mossavar-Rahmani, Yasmin; Siega-Riz, Anna María; Gallo, Linda C; Wassertheil-Smoller, Sylvia; Kaplan, Robert C; Corsino, Leonor
ABSTRACT: Background: Both the incidence of diabetes mellitus and consumption of sugar-sweetened beverages are high in the Hispanic/Latino population in the United States. The associations between consumption of sugar-sweetened beverages, artificially sweetened beverages, and 100% fruit juice with prediabetes and glucose metabolism markers in the diverse Hispanic/Latino population in the United States are unknown. Objectives: The objective of this study was to examine the cross-sectional associations between consumption of sugar-sweetened beverages, artificially sweetened beverages, and 100% fruit juice with prediabetes and glucose metabolism markers such as fasting glucose and insulin, 2-h oral-glucose-tolerance test, HOMA-IR, HOMA index for β-cell function (HOMA-B), and glycated hemoglobin (HbA1c) among US Hispanic/Latino adults. Methods: Using baseline data from the Hispanic Community Health Study/Study of Latinos (2008–2011), beverage consumption was ascertained using two 24-h dietary recalls and a food propensity questionnaire. Diabetes/prediabetes status was defined by self-report, antihyperglycemic medication use, and American Diabetes Association laboratory criteria. Among 9965 individuals without diabetes (5194 normoglycemia, 4771 prediabetes) aged 18–74 y, the associations of beverage consumption with prediabetes and glucose metabolism markers were analyzed using logistic and linear regressions, respectively, accounting for complex survey design. Results: Compared with individuals who consumed <1 serving/d (<240 mL/d) of sugar-sweetened beverages, individuals who consumed >2 servings/d (>480 mL/d) had 1.3 times greater odds of having prediabetes (95% CI: 1.06, 1.61) and higher glucose metabolism markers including fasting glucose, fasting insulin, HOMA-IR, and HbA1c. Consumption of artificially sweetened beverages showed an inverse association with β-cell function (HOMA-B). Intake of 100% fruit juice was not significantly associated with prediabetes nor with glucose metabolism markers. Conclusions: Among US Hispanic/Latino adults, higher sugar-sweetened beverage consumption was associated with increased odds of prediabetes and higher glucose metabolism markers. Public health initiatives to decrease sugar-sweetened beverage consumption could potentially reduce the burden of diabetes among Hispanics/Latinos in the United States.